Perspective of Online Media towards Settlement Development Case in Bekasi using Agenda Setting Models - Tatik Yuniarti; Amiruddin Saleh; Musa Hubeis; Rilus Kinseng (Jurnal Pekommas, 2018)
Development does not always have a positive impact on the surroundings, but also negative impacts often occur. Social change of society one of them is the impact of the development. Therefore, the purpose of this study is to analyze how the development and social change of Bekasi society takes place from the perspective of discourse in the mass media. The method used is to use qualitative data analysis that comes from news in mass media. The reports were analyzed using Nvivo 11 software assistance. The results of the analysis revealed that the government needed to review and evaluate the permit for the development of apartments and the area, because it had a major social change effect on the surrounding community. From the news in mass media shows that the surrounding communities are much negatively affected by the development. The media agenda, the government agenda and the public agenda are related to the occurrence of social change.